Children and Teens in Charge of their Health (CATCH): A protocol for a feasibility randomised controlled trial of solution-focused coaching to foster healthy lifestyles in childhood disability. Issue 3 (4th March 2019) - McPherson, Amy C; Biddiss, Elaine; Chen, Lorry; Church, Paige Terrien; de Groot, Janke F; Keenan, Sarah; King, Gillian; Lui, Toni; Maltais, Desiree B; Mérette, Chantal; Moffet, Hélène; Moola, Fiona; et al.
Abstract : Introduction: Children with physical disabilities are rarely included in interventions to promote healthy lifestyles, despite being at higher risk for suboptimal dietary and physical activity behaviours. The Children and Teens in Charge of their Health study explores the feasibility and acceptability of conducting a randomised controlled trial (RCT) of a strengths-based, solution-focused coaching intervention for improving and sustaining physical activity and healthy dietary habits in children and young people with physical disabilities. Methods and analysis: Thirty children aged 10–18 years with a diagnosis of spina bifida or cerebral palsy who are able to set healthy lifestyle goals will be recruited from two children's rehabilitation hospitals in Ontario, Canada. Participants will be enrolled in the study for twelve months. All participants will receive standard care and printed information about healthy lifestyles. Of the 30 participants, 15 will be randomised to receive a coaching intervention for the first 6 months. Health indicators and psychosocial outcomes will be assessed by blinded assessors four times: at the start of the trial, immediately postintervention (6 months after randomisation), and at 3 and 6 months postintervention (9 and 12 months after randomisation, respectively). Predefined success criteria will be used to assess the feasibility of trial processes such as recruitment, attrition, stratification and intervention fidelity. Acceptability and perceived impact of the intervention will be explored qualitatively. Ethics and dissemination: The study has been approved by Holland Bloorview Kids Rehabilitation Hospital's Research Ethics Board (Ref: 17–752). A knowledge translation planning template will be used to ensure our findings have maximum reach. Trial registration number: NCT03523806.